SrBa2(NH2)6: A New Ternary Amide from Ammonothermal Synthesis1. Issue 2 (25th November 2014) - Hertrampf, Jan; Alt, Nicolas S. A.; Schlücker, Eberhard; Niewa, Rainer
Abstract Single crystals of SrBa2(NH2)6 were obtained from the reaction of barium and strontium metal under ammonothermal conditions at a pressure of 180 MPa and a temperature of 573 K. The crystal structure [a = 6.395(2) Å, b = 7.195(2) Å, c = 10.471(2) Å, β = 97.99(2)°, Z = 2, V = 477.13(2) Å3, P21/n] contains Ba in sevenfold and Sr in octahedral coordination by amide ions, similar to the enviroments of these metal ions in the binary amides. Further, IR and Raman data are reported.